Quality improvement of childbirth care (Adequate Birth Project) and the assessment of women's birth experience in Brazil: a structural equation modelling of a cross-sectional research - Mariza Miranda Theme Filha; Tatiana Henriques Leite; Marcia Leonardi Baldisserotto; Ana Paula Esteves-Pereira; Maria do Carmo Leal (BMC, 2022)
Abstract Background Brazil's maternity care is highly medicalized, and obstetric interventions in labour and birth are high, mainly in private health system. The Adequate Birth Project (PPA-Projeto Parto Adequado) is quality improvement project designed to reduce unnecessary caesarian section rates in private hospitals in Brazil. This study evaluated the association between the participation of the PPA and the birth experience assessed by the women. Methods It was carried out in 2017/2018 a hospital-based research with a convenience sample of 12 private hospitals among the 23 participants of the project. In this article, a sub-sample of 2348 mothers of 4878 postpartum women, including only women who desired vaginal birth at the ending of pregnancy was analyzed. Multigroup structural equation modelling was used for data analysis to compare vaginal birth and caesarean section. The latent variable was constructed from four items: participation in decisions, respectful treatment during labour and birth, satisfaction with the care during childbirth, satisfaction with care of the baby. Results In the vaginal birth group, women who participated in PPA rated the birth experience better than women who did not participate (standardized coefficient: 0.388, p-value: 0.028). On the other hand, this effect was not observed (standardized coefficient: − 0.271, p-value: 0.085) in the caesarean section. Besides, the explicative models for a good birth experience varied to the type of childbirth. Among women with vaginal birth, complication during pregnancy and younger age were associated with a more positive birth experience. In contrast, for women with a caesarean section, access to information and participation in the pregnant group was associated with a better evaluation of the birth experience. Conclusions The childbirth care model that encourages vaginal delivery and reduces unnecessary caesarean modulates the birth experience according to the type of birth. This study also highlights the importance of perceived control, support, and relationship with the health team shaping women's experience with labour and delivery. These factors may affect policy, practice, and research on childbirth care.